Trends in Statistical Codicology - Maniaci, Marilena (Studies in Manuscript Cultures, 2021)
The application of statistical techniques to the study of manuscript books, based on the analysis of large data sets acquired through the archaeological observation of manuscripts, remains to this day one of the most original trends in codicological research. This volume aims to present, in English translation, a series of recent and significant papers by means of which the statistical approach continues to demonstrate its vast potential.